(untitled) ("Conference on Universal Science Research 2023", 2023)
Most of the vegetable cultivar families Nightshade food from the Central American or South American center, and therefore, the desire for growing conditions All these factors are indispensable, but equivalent. A complex of external effects affecting the association of plants into 4 groups: